2014
DOI: 10.1371/journal.pone.0106920
|View full text |Cite
|
Sign up to set email alerts
|

Do You Hear the Same? Cardiorespiratory Responses between Mothers and Infants during Tonal and Atonal Music

Abstract: This study examined the effects of tonal and atonal music on respiratory sinus arrhythmia (RSA) in 40 mothers and their 3-month-old infants. The tonal music fragment was composed using the structure of a harmonic series that corresponds with the pitch ratio characteristics of mother–infant vocal dialogues. The atonal fragment did not correspond with a tonal structure. Mother–infant ECG and respiration were registered along with simultaneous video recordings. RR-interval, respiration rate, and RSA were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 73 publications
0
23
0
1
Order By: Relevance
“…The distinction between the two versions’ factor structure presumably reflects differences in the extent to which parents of different age groups engage in the two activities. Clearly, infants until the age of 2 years engage in active music—making to a lesser extent, while parental singing appears to hold a central role in regulating arousal [ 21 ] and building emotional interaction [ 76 77 ] in infancy. Furthermore, approaching singing in infancy as a separate dimension highlights the importance that this activity may carry for developmental outcomes such as socio-emotional and communicative development [ 78 ] and language learning [ 24 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinction between the two versions’ factor structure presumably reflects differences in the extent to which parents of different age groups engage in the two activities. Clearly, infants until the age of 2 years engage in active music—making to a lesser extent, while parental singing appears to hold a central role in regulating arousal [ 21 ] and building emotional interaction [ 76 77 ] in infancy. Furthermore, approaching singing in infancy as a separate dimension highlights the importance that this activity may carry for developmental outcomes such as socio-emotional and communicative development [ 78 ] and language learning [ 24 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that infants benefit from the combined input of music and lyrics, since a second source of information (music) provides additional cues to help them identify structure in the first source (words and syllables) [ 25 ]. Furthermore, Van Puyvelde and Franco [ 78 ] have proposed that the melodic patterns and moments of ‘tonal synchrony’ observed in parent-infant vocal interactions [ 79 ], which facilitate affective co-regulation [ 77 ] may well be a prerequisite for later social development. Therefore, since one of the key aims of developing the Music@Home questionnaire is its future use in experimental research, addressing the potential effects that aspects of the home musical environment may have on development, including parental singing as a separate subscale for the infant version is well motivated and supported by existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, infants display superior attention to sung than spoken infant-directed communication (Nakata and Trehub, 2004; Tsang et al, 2017). Similarly, musical characteristics of mother–infant vocal interactions are critical in promoting the development of socio-emotional regulation (Trevarthen, 1999; Dissanayake, 2000; Van Puyvelde et al, 2014). Finally, the acquisition of musical and linguistic features such as rhythm entrainment and vocal learning may rely on common learning mechanisms with adaptive value for social development, such as imitation (Carpenter, 2006; Fitch, 2013; Laland et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of atonality on autonomic parameters has been rarely investigated, except for a study in which the respiratory sinus arrhythmia was measured in 40 mothers and their infants while listening to tonal and atonal music ( Van Puyvelde et al, 2014 ). The authors found no effect of atonal music in mothers but only in infants.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be known that the study’s aim was not to establish to what extent the esthetic appreciation depended on evolutionary, anatomical or physiological constraints or whether it was influenced by cultural, historical, and individual differences ( Konecni, 1979 ; Jacobsen, 2010 ). To follow an ecological approach, we chose to make the participants listen to real tonal or atonal artworks and masterpieces, instead of presenting them simple melodies, chords, or fragments of little artistic value (see Van Puyvelde et al, 2014 ; Krabs et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%